The Role of Service Quality, Price, and Product Quality in Influencing Purchase Decision at Café with Classic Atmosphere in Kampung Heritage - Karnawati, Tin Agustina (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The developing businesses of cafe and restaurant are recently employing various certain concepts or themes, including the concept of a cafe with classic atmosphere. This is inseparable from the emergence of similar business competition, thus an applicable marketing strategy is needed to understand the consumer’s behavior. Cafes with classic atmospheres, as one of the coffee shop-based cafes located in a Kampung Heritage area with a fairly dense environment, limited parking space, and competition with similar cafes, are business challenges to survive. The purpose of this study is to determine the relationship between variables that influence purchase decisions. Research variables include service quality (X1), price (X2), and product quality (X3) as independent variables and purchase decisions (Y) as dependent variables, and each variable will be measured by indicators. The type of research uses a causal research design with a quantitative approach and primary data is obtained from 100 respondents using Accidental Sampling techniques. The data analysis method uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The research results show that service quality, price, and product quality partially have a positive and significant effect on purchase decisions.